Contracts, Job Experience, and Cyclical Labor Market Adjustments - Raisian, John (Journal of Labor Economics, 1983)
Longitudinal estimates of the variability of individual wages, hours, and weeks worked over the course of changing demand states are provided for all workers generally and for workers of varied levels of job experience. Emphasis is placed on that part of job experience represented as years on current job, a commonly used proxy for the magnitude of firm-specific skills. Interpretation of resulting estimates in the context of the labor market contracting literature is attempted. Generally significant procyclical patterns are found for real weekly wages, weekly hours, and weeks worked. The extent of weekly wage variability is much greater than is generally suggested in the literature. Furthermore, workers with greater tenure exhibit greater cyclical wage and hours variability and less weeks variability. Finally, empirical distinctions are drawn separately for white-collar and blue-collar as well as union and nonunion workers.